2012
DOI: 10.1089/jmf.2011.0043
|View full text |Cite
|
Sign up to set email alerts
|

7-Epiclusianone, the Natural Prenylated Benzophenone, Inhibits Superoxide Anions in the Neutrophil Respiratory Burst

Abstract: Despite defenses by polymorphonuclear neutrophils in the host against invading agents, overproduction of oxidant species by phagocytes can lead to damage in the surrounding tissues. Several benzophenones have been shown to possess anti-inflammatory properties. The effect of the natural benzophenone 7-epiclusianone isolated from leaves of Garcinia brasiliensis was investigated by using in vitro antioxidant and ex vivo anti-inflammatory assays, focusing on the neutrophil respiratory burst and on the biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…The observed results, showing the presence in both fruits and leaves of flavonoids, biflavonoids, catechins, xanthones, and others, corroborate the importance of phenolic compounds as promising active components. For several of the compounds found in the extracts of fruits and leaves, studies have attributed the following bioactive potentials: Antioxidant [33][34][35], antiproliferative, and apoptotic [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed results, showing the presence in both fruits and leaves of flavonoids, biflavonoids, catechins, xanthones, and others, corroborate the importance of phenolic compounds as promising active components. For several of the compounds found in the extracts of fruits and leaves, studies have attributed the following bioactive potentials: Antioxidant [33][34][35], antiproliferative, and apoptotic [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The ethanolic extracts were dissolved in methanol to obtain a concentration of 0.5 mg/solids/mL −1 and then analyzed. The total amount of phenols in each extract was quantified using a standard curve prepared with gallic acid and expressed as gallic acid equivalent (GAE) [37].…”
Section: Determination Of Total Phenolsmentioning
confidence: 99%
“…In this context, it is not always noted that antioxidant values are determinants of the antimutagenic potential of products. A study by Santa-Cecília et al (2012) with MI has shown that, even as low antioxidant activity, the MI was able to down regulate inflammatory phagocyte superoxide anion release through a mechanism controlled by protein tyrosine phosphorylation and by the direct stimulation of the protein kinase C.…”
Section: In Vivo Mutagenic Test In Micementioning
confidence: 99%
“…7-epiclusianone has shown important biological effects including anti-inflammatory [ 7 , 8 ], antinociceptive [ 7 , 9 ], antimicrobial [ 10 , 11 ], antispasmodic [ 12 ], antianaphylactic [ 13 ] and antiprotozoal activities [ 14 ]. On the other hand, the potential anticancer and apoptotic effect is underexplored.…”
Section: Introductionmentioning
confidence: 99%